Risk Factors for Nonresilient Outcomes in Older Adults After Total Knee Replacement. Issue 9 (4th September 2021) - Laskow, Thomas; Zhu, Jiafeng; Buta, Brian; Oni, Julius; Sieber, Frederick; Bandeen-Roche, Karen; Walston, Jeremy; Franklin, Patricia D; Varadhan, Ravi
Abstract: Background: Total knee replacement (TKR) is a common procedure in older adults. Physical resilience may be a useful construct to explain variable outcomes. We sought to define a simple measure of physical resilience and identify risk factors for nonresilient patient outcomes. Methods: Secondary analysis of Function and Outcomes Research for Comparative Effectiveness in Total Joint Replacement (FORCE-TJR) cohort study, a prospective registry of total joint replacement. The analysis included 7 239 adults aged 60 or older who underwent TKR between 2011 and 2015. Measures included sociodemographic and health factors. Outcomes were categorized as physically resilient versus nonresilient based on the change from baseline to 1-year follow-up for 3 patient-reported outcomes: the physical component summary (PCS), bodily pain (BP), and vitality (VT) from the Short Form-36 subcomponent scores, at preop and 1-year postprocedure. Associations were expressed as relative risk (RR) of physically nonresilient outcomes using generalized linear regression models, with Poisson distribution and log link. Results: Age, body mass index, and Charlson Comorbidity Index (CCI) were associated with increased risk of physically nonresilient outcomes across PCS, BP, and VT: age, per 5 years for PCS (RR = 1.18 [1.12–1.23]), BP (RR = 1.06 [1.01–1.11), and VT (RR = 1.09 [1.06–1.12]); body mass index, per 5 kg/m 2, for PCS (RR = 1.13 [1.07–1.19]), BP (RR = 1.06 [1.00–1.11]), and VT (RR = 1.08 [1.04–1.11]); and CCI for PCS CCI = 1 (RR = 1.38 [1.20–1.59]), CCI = 2–5 (RR = 1.59 [1.35–1.88]), CCI ≥6 (RR = 1.55 [1.31–1.83]. Household income >45 000 associated with lower risk for PCS (RR = 0.81 [0.70–0.93]), BP (RR = 0.80 [0.69–0.91]), and VT (RR = 0.86 [0.78–0.93]). Conclusions: We operationalized physical resilience and identified factors predicting resilience after TKR. This approach may aid clinical risk stratification, guide further investigation of causes, and ultimately aid patients through the design of interventions to enhance physical resilience.